2013
DOI: 10.1186/1471-2180-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional cross-activation between toxin-antitoxin systems of Escherichia coli

Abstract: BackgroundBacterial toxin-antitoxin (TA) systems are formed by potent regulatory or suicide factors (toxins) and their short-lived inhibitors (antitoxins). Antitoxins are DNA-binding proteins and auto-repress transcription of TA operons. Transcription of multiple TA operons is activated in temporarily non-growing persister cells that can resist killing by antibiotics. Consequently, the antitoxin levels of persisters must have been dropped and toxins are released of inhibition.ResultsHere, we describe transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 74 publications
(91 reference statements)
6
66
0
Order By: Relevance
“…12,45,55,56 Recent studies have demonstrated that TA-II systems can affect positively or negatively the expression of other TA-II modules. 39,57,58 However in these studies, only changes in steady-state RNA levels have been shown, and RNA synthesis (transcription) and RNA stability effects cannot be distinguished. In our experiments, direct RNA stability measurements rule out stability effects of MazE and MazEF on RatA, since the RatA half-life is independent of MazE and MazEF levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,45,55,56 Recent studies have demonstrated that TA-II systems can affect positively or negatively the expression of other TA-II modules. 39,57,58 However in these studies, only changes in steady-state RNA levels have been shown, and RNA synthesis (transcription) and RNA stability effects cannot be distinguished. In our experiments, direct RNA stability measurements rule out stability effects of MazE and MazEF on RatA, since the RatA half-life is independent of MazE and MazEF levels.…”
Section: Discussionmentioning
confidence: 99%
“…For instance in E. coli, the TA-II endoribonuclease toxin MsqR was shown to enhance a selective degradation of the ghoST mRNA in favor of the type V TA toxin GhoT, by direct cleavage within the ghoS sequence and, a complex regulatory interplay has been unveiled between several TA-II modules. 38,39 These observations suggest that together TAs may mediate concerted physiological responses in the cell.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…HipA activity triggers ppGpp, which may then induce the development of persistence through the activation of other toxins which do not rely upon the maintenance of high ppGpp for antibiotic tolerance. It was recently shown that overexpression of HipA triggers the transcriptional activation of other TA modules (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of TA systems on bacterial fitness can be seen when multiple TA loci have been deleted from the chromosome, indicating that chromosomal TA systems constitute a redundant network (21). As shown recently, the coordinated activation of the TA network in E. coli involves increased activity of the Lon protease that is triggered by the stringent response (15,23). Transcriptional cross-activation between different TA systems has also been suggested as a mechanism for a synchronized response (23).…”
mentioning
confidence: 99%